ANALISIS ELEMEN BERKEBINEKAAN GLOBAL PADA MODUL AJAR PKN KELAS IV SEKOLAH DASAR - Puji Arini, Wulan; Sarah fazila; Rahmiaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The teaching module is an important instrument in the implementation of the Merdeka Curriculum, especially in instilling character values ​​in elementary school students. This study aims to analyze the integration of global diversity elements in the Civic Education (PKN) teaching module for grade IV at SD Negeri 1 Syamtalira Bayu. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the teaching module has included elements such as tolerance, cross-cultural awareness, respect for human rights, social justice, empathy, and mutual cooperation. The value of tolerance towards regional language diversity is the most dominant element raised in the module. These elements not only appear explicitly in the contents of the module, but are also reflected in classroom learning practices, although there are still challenges in even implementation. These findings indicate that the integration of global values ​​associated with the local context can strengthen inclusive learning and be oriented towards the formation of students' character as global citizens. This study contributes to the development of teaching modules that are not only academically relevant, but also strategic in building a tolerant, inclusive, and civilized generation.